Analisis Faktor-Faktor Yang Memotivasi MinatMahasiswa Dalam Berwirausaha(Studi Kasus Mahasiswa FEB Universitas Muhammadiyah Surakarta) - Putra, Redika Dewangga; , Nur Achmad, S.E., M.Si (2017)
This study aimed to examine the effect of risk tolerance, boost self success, freedom in work and employment background of parents of interest in entrepreneurship. Testing the hypothesis in this study using regression analysis moderating with t-test, F and coefficient of determination (R2). The population of this research is the S1 students of the Faculty of Economics and Business, University of Muhammadiyah Surakarta. The sample in this study was 100 students S1 Faculty of Economics and Business Muhammadiyah University of Surakarta who have attended entrepreneurship courses. Based on the survey results revealed that tolerance would risk a significant effect on student interest in entrepreneurship, so that H 1 is accepted. Encouragement significantly influence the success of self-interest of students to entrepreneurship, so that H 2 is accepted. Freedom of the work does not affect the interest of students to entrepreneurship, this suggests that the entrepreneurial bukanlan job easy and free to do anyone, even though it seems there is freedom in the work, but the reality in entrepreneurship requires a strong commitment from the inside, so that the H 3 is rejected. Employment background of parents significantly influence the interest of students to entrepreneurship, so H 4 is accepted. Keywords: torelansi the risks, the success of self-encouragement, freedom of work, the background of the work of parents, interest in entrepreneurship.